(3eNJUQ QjGV GdfahS aj WHbGJ YdeGA eOjfg GdbjQhGfs - (3jMji Hf EHQGgje Hf Ydis; (3YHO Gddg Hf eMeO Hf YHO Gddg GdeGdcj, CHh HcQ,J (B453 (3g` s ((3CMeOGdCRgQi s)
(3ChdgG (B:s
(3hHYO agPG eNJUQ ef QjGV GdfahS ai WHbGJ YdGA eOjfg bjQhGf CaQjbjI heGjdjg, s
(3BNQgG (B:s
(3hcGf ai LedI GdfaQ Gd(B\(3jf bGdhG s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B121 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B129s
Keywords: (3GdJGQjNs